2018
DOI: 10.3390/ijerph15020269
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Pharmaceutical and Personal Care Products (PPCPs) from Municipal Waste Water with Integrated Membrane Systems, MBR-RO/NF

Abstract: This study focuses on the application of combining membrane bioreactor (MBR) treatment with reverse osmosis (RO) or nanofiltration (NF) membrane treatment for removal of pharmaceuticals and personal care products (PPCPs) in municipal wastewater. Twenty-seven PPCPs were measured in real influent with lowest average concentration being trimethoprim (7.12 ng/L) and the highest being caffeine (18.4 ng/L). The results suggest that the MBR system effectively removes the PPCPs with an efficiency of between 41.08% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Furthermore, both NF and RO in the study also demonstrated a high removal rate (>80%) of compounds that persist through MBR including DEET, Atrazine, Meprobamate, Primidone, and Dilantin. This result is strongly supported by another MBR-NF/RO evaluation, where 27 common antibiotics and pharmaceuticals were tested, showing an excellent removal rate of the system for all compounds (95% on average) and a high removal rate (>50%) of NF for Metoprolol, Norfloxacin, Enrofloxacin, and Carbamazepine compounds [19]. With regard to the removal of pathogens, NF has been shown to be able to remove Bacillus subtilis bacteria and MS2 bacteriophage at very high efficiencies, ranging from 3.3 to 6.3 log removal value (LRV) for Bacillus subtilis bacteria and from 4.1 to 4.5 LRV for MS2 bacteriophage [20].…”
Section: Introductionsupporting
confidence: 61%
“…Furthermore, both NF and RO in the study also demonstrated a high removal rate (>80%) of compounds that persist through MBR including DEET, Atrazine, Meprobamate, Primidone, and Dilantin. This result is strongly supported by another MBR-NF/RO evaluation, where 27 common antibiotics and pharmaceuticals were tested, showing an excellent removal rate of the system for all compounds (95% on average) and a high removal rate (>50%) of NF for Metoprolol, Norfloxacin, Enrofloxacin, and Carbamazepine compounds [19]. With regard to the removal of pathogens, NF has been shown to be able to remove Bacillus subtilis bacteria and MS2 bacteriophage at very high efficiencies, ranging from 3.3 to 6.3 log removal value (LRV) for Bacillus subtilis bacteria and from 4.1 to 4.5 LRV for MS2 bacteriophage [20].…”
Section: Introductionsupporting
confidence: 61%
“…Pharmaceuticals and personal care products (PCPs) comprise numerous chemical classes. Pharmaceuticals and PCPs contain a large and diverse group of organic compounds, including endocrine disrupting compounds and pharmaceutically active compounds [34] with a significant impact on water ecology and human health [35]. Current wastewater treatment procedures have the capacity to eliminate only partially Pharmaceuticals and PCPs and, therefore, they will be found in receiving waters or in the resulting sludge which is sometimes used as fertilizer [36].…”
Section: Effects Of Waste Cooking Oil Pharmaceuticals and Other Chemmentioning
confidence: 99%
“…The results suggested that the integrated membrane systems can achieve even higher removal rates of above 95% for most of them. Further studies showed that MBR-RO achieved even better results with the removal of 20 compounds to below detection limits as compared to 13 compounds by MBR/NF [72]. A study conducted by Baransi-Karkaby et al reported the improved rejection of multiple EDCs and pharmaceutically active compounds (PhACs) by RO membrane elements using concentration polarization-and surfactant-enhanced surface polymerization [73].…”
Section: Agricultural Waste Emerging Contaminants Referencesmentioning
confidence: 99%